Potencial geoparque do polo turístico das Águas de São Lourenço - Mato Grosso - Godoy, Laís Paciência [UNESP] (2014)
The Thermal Water of the Touristic Polo of Águas de São Lourenço occur in the municipalities of São Vicente, Juscimeira and Jaciara, southeastern Mato Grosso 150 km from Cuiabá. The work aims to generate information in the field of geoscience to support geotourism in the region based mainly on thermal and surface mineral water resources, as well as propose solutions from a survey of tourism potential of local attractions and to consider solutions that facilitate the elaboration of a Geoparque for the region. The impact of tourism activities were evaluate by applying the VIM (Visitor Impact Management) method with emphasis on biophysical indicators. The region is located in the units of Guimarães Plateau that presents features of cuesta relief of Serra dos Coroados and São Jerônimo and by Rondonóplis Depression formed by the São Lourenço River valley, where are exposed rocks of the Paraná Basin (Furnas, Ponta Grossa, Aquidauna, Botucatu and Serra Geral Formation). The geological and hydric characteristics contributed to the hydrothermal conditions of Furnas sandstone aquifer considering that the region present geomorphological features defined by exuberant relief forms, resulting in the presence of mountains and caves. The intense water surface resource, result in numerous waterfalls and rapids, with immense possibilities for the practice of contemplative tourism and ecotourism. The health resort is a major tourist hub for the state of Mato Grosso and the municipalities survive economically on tourism, which depends on the infiltration of rainwater for renovation of the main product, surface and thermal spring. Thus, keeping this heritage means to contribute to the preservation of natural resource so rare, checking the consequences and benefits of tourism based on ownership and exploitation so essential to the region's economy